True legend - Lupica, Mike (Philomel Books, 2012)
Fifteen-year-old Drew "True" Robinson loves being the best point-guard prospect in high school basketball, but learns the consequences of fame through a former player, as well as through the man who expects to be his manager when True reaches the NBA.